MASQUERADE OF FEMININITY AND MASCULINITY IN JAPANESE COMIC MIDORI IS A TOMBOY AND W-JULIET - Agnessia Shella Dinata; Jenny M. Djundjung (Institute of Research and Community Outreach - Petra Christian University, 2014)
Masquerade is the use of mask and disguise by a person to hide a certain identity and make a new identity. The concept of masquerade that is the use of mask has been used in Japanese theatre such as Kabuki and Takarazuka; however those theatres also use the concept of gender bender. Nowadays, the two concepts are applied in Japanese comic that is popular in teenager. In this study, I would like to analyze the use of mask and gender bender by Makoto and Midori in Japanese comic W-Juliet and Midori is a Tomboy. I would like to reveal the strategy that is used by Makoto and Midori in wearing their mask and the meaning of the masks that they use. By this study, I will prove that femininity and masculinity are not related by sex and can be used as mask to create a new identity.